PELAKSANAAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN APARTEMEN BERDASARKAN PERATURAN GUBERNUR DKI JAKARTA NOMOR 132 TAHUN 2018 TENTANG PEMBINAAN PENGELOLAAN RUMAH SUSUN MILIK - Hasita Zhafirah Saraswati; Endang Pandamdari (Jurnal Hukum Adigama, 2020)
Land and Building Tax (PBB) is a tax that is imposed on each building that is or is an object of tax. The land and building tax on apartments is regulated in DKI Jakarta Governor Regulation No. 132 of 2018, in Article 88 it is explained that the land and building tax is the cost of the apartment units that must be paid personally by the owner or occupant of the apartment. This thesis research uses a qualitative approach and descriptive type. The research data collection technique was carried out by interviewing competent lecturers in tax law. The results obtained are the collection of land and apartment building tax based on the DKI Jakarta governor's regulation, which is paid personally by the owner or occupant of the apartment after the issuance of the tax notification letter (SPPT) by the relevant agency. In the land and building tax collection activities, of course there is a need for cooperation and communication between the taxpayer, the government, and also the management so that the land tax collection and apartment construction runs well so that there are no deficiencies in its implementation.